2017
DOI: 10.1038/onc.2017.175
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy suppresses Ras-driven epithelial tumourigenesis by limiting the accumulation of reactive oxygen species

Abstract: Activation of Ras signalling occurs in ~30% of human cancers; however, activated Ras alone is not sufficient for tumourigenesis. In a screen for tumour suppressors that cooperate with oncogenic Ras (RasV12) in Drosophila, we identified genes involved in the autophagy pathway. Bioinformatic analysis of human tumours revealed that several core autophagy genes, including GABARAP, correlate with oncogenic KRAS mutations and poor prognosis in human pancreatic cancer, supporting a potential tumour-suppressive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 87 publications
2
31
1
Order By: Relevance
“…The ROS indicator dihydroethidium (DHE) strongly labels scrib −/− Ras V12 mutant clones in mosaic discs, while wild-type (wt), scrib −/− and Ras V12 -expressing clones are not labeled by DHE or very little ( Figure 1A–D’ ; quantified in Figure 1F ; see also Figure 2A,A’ ). Similar results were reported recently ( Katheder et al, 2017 ; Manent et al, 2017 ). A different ROS indicator, H 2 DCF-DA, confirms these results ( Figure 1—figure supplement 1A–C,G ).…”
Section: Resultssupporting
confidence: 93%
“…The ROS indicator dihydroethidium (DHE) strongly labels scrib −/− Ras V12 mutant clones in mosaic discs, while wild-type (wt), scrib −/− and Ras V12 -expressing clones are not labeled by DHE or very little ( Figure 1A–D’ ; quantified in Figure 1F ; see also Figure 2A,A’ ). Similar results were reported recently ( Katheder et al, 2017 ; Manent et al, 2017 ). A different ROS indicator, H 2 DCF-DA, confirms these results ( Figure 1—figure supplement 1A–C,G ).…”
Section: Resultssupporting
confidence: 93%
“…In these confirmation assays, downregulation of eighty out of the 100 retested genes resulted in increased hyperplasia of the eye epithelium, using an arbitrary cut off of an average score of 0.75 or above, specifically in the presence of constitutively activated dRas V12 ( Fig 3B and 3C ; S5 Table ). It should be noted that although some of the RNAi lines tested were KK RNAi lines (indicated by KK in S5 Table ), some of which may overexpress the tiptop ( tio ) gene and result in potentially aberrant effects [ 27 ], we have previously shown that tio overexpression does not modify the ey>dRas V12 phenotype [ 28 ]. Thus, the results from the KK lines tested, which mostly confirmed the results of GD lines, are valid.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, several genes and pathways identified in our primary screen have an effect on oxidative stress levels or proper mitochondrial function: detoxifying enzymes such as Gutathione S Transferases or Wwox [ 64 ], and many mitochondrial genes, the loss of which can potentially impede proper mitochondrial function and generate oxidative stress. Interestingly, we have recently shown that increased oxidative stress levels induced by autophagy impairment can indeed cooperate with oncogenic Ras by triggering the JNK stress response pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has a double-edged sword effect in cancer [2,3]. Autophagy's tumor suppressive function is partly attributed to its ability to induce cell death via several mechanisms [4,5]; however, a positive role of autophagy in tumorigenesis has also been established. Emerging studies have shown that the RAS signalling pathway is one of the oncogenic pathways influenced by autophagic activity [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%